COMPARATIVE STUDY OF SUPPLY CHAIN STRATEGY IN STUDENT ENTREPRENEURSHIP UNESA INDONESIA AND UPSI MALAYSIA - Kurniawan, Riza Yonisa; Trisnawati, Novi; Soesatyo, Yoyok; Jusoh, Osman (International Journal of Supply Chain Management, 2019)
Abstract- The aim of this study is to compare entrepreneurship lessons on student entrepreneurship attitudes between the Economic Education Department, Faculty of Economics, State University of Surabaya (UNESA), Indonesia and Faculty of Management and Economics, University of Education Sultan Idris (UPSI), Malaysia. This quantitative study used a comparative study method of entrepreneurship lesson activities in UNESA Indonesia and UPSI Malaysia. Differences in entrepreneurship learning between UNESA and UPSI students were measured by learning atmosphere, interest in entrepreneurship, and entrepreneurship attitude. The difference in learning atmosphere was due to the differences in culture and curriculum between countries, where entrepreneur lesson of UPSI students was taught early on in the course of study, while new UNESA students are taught in the fifth semester. There was a difference in entrepreneurial learning in the Department of Economic Education of the Faculty of Economics of Surabaya with the Faculty of Management and Economics of University of Education Sultan Idris, Malaysia. This research provides a vision for the academic community in determining the proper learning design to foster the character and attitude for entrepreneurship in the students.